Eye and the Beholder : the Depiction of the Eye in Western Sculpture with Special Reference to the Period 1350-1700 and to Colour in Sculpture /: the Depiction of the Eye in Western Sculpture with Special Reference to the Period 1350-1700 and to Colour in Sculpture. (2014) - Hägele, Hannelore
No abstract available